gh bisects fgi. solve for fgi,fgh,hgi solve for x Simplify all answers
![gh bisects fgi solve for fgifghhgi solve for x Simplify all answers class=](https://us-static.z-dn.net/files/d57/1f65cb6e30e797bd628793acf1434878.jpg)
Answer:
fgi = 48
fgh = 24
hgi = 24
Step-by-step explanation:
Bisection divides an angle into two equal angles,
So,
4x - 20 = 3x - 9
4x - 3x = - 9 + 20
x = 11
fgi = 3x - 9 + 4x - 20
= 3x + 4x - 20 - 9
= 7x - 29
= 7 ( 11 ) - 29
= 77 - 29
fgi = 48
fgh = 3x - 9
= 3 ( 11 ) - 9
= 33 - 9
fgh = 24
hgi = 4x - 20
= 4 ( 11 ) - 20
= 44 - 20
hgi = 24